Optimizing the thermostability of triketone dioxygenase for engineering tolerance to mesotrione herbicide in soybean and cotton - Duff, Stephen M. G.; Shi, Lei; Chen, Danqi; Fu, Xiaoran; Peng, Mingsheng; Larue, Clayton T.; Weihe, Janice; Koczan, Jessica; Krebel, Brian; Qi, Qungang (Frontiers in Plant Science, 2025)
Optimized triketone dioxygenase (TDO) variants with enhanced temperature stability parameters were engineered to enable robust triketone tolerance in transgenic cotton and soybean crops. This herbicide tolerance trait, which can metabolize triketone herbicides such as mesotrione and tembotrione, could be useful for weed management systems and provide additional tools for farmers to control weeds. TDO has a low melting point (~39°C–40°C). We designed an optimization scheme using a hypothesis-based rational design to improve the temperature stability of TDO. Temperature stabilization resulted in enzymes with Kcat values less than half of wild-type TDO. The best variant TDO had a Kcat of 1.2 min−1 compared to wild-type TDO, which had a Kcat of 2.7 min−1. However Km values did not change much due to temperature stabilization. Recovery of the Kcat without losing heat stability was the focus of additional optimization. Multiple variants were found that had better heat stability in vitro and efficacies against mesotrione equaling the wild-type (WT) TDO in greenhouse and field tests.